How to achieve team cohesion through competition in sport: an organizational model - Smith, J. K. (The Sport Journal, 2015)
The purpose of this paper is to conceptualize a practical method for coaches of any sport team to improve team performance and cohesion through inter-squad competition and intra-squad cooperation. While the concept of intra-team competition to improve cohesion and team performance is not new, this paper describes a practical, task driven approach for coaches to use. For purposes of clarity, American football is the example used to describe this approach. Although, this task driven competition format can be applied to other sports teams, American football has more distinctive task oriented positions than other sports, thus providing simplicity. Also, football teams use the most formal off-season competitive scrimmage strategies in which the first team offense and first team defense play each other in order for the coaching staff to assess players and test game schemes. This widespread tactic is useful for coaches, but it can be argued this creates division with the rest of the team. In-fighting among the individuals in each squad (i.e. wide receivers, offensive line, etc…) can prevail, and a counter-productive attitude may develop that breaks any cohesive advantage gained as players begin to focus on the amount of playing time they get in relation to their teammates. However, if coaching staffs adopt a task oriented system in which the squad coaches encourage group success and teamwork, and the coordinator level harnesses the competitive spirit, players will be more likely to encourage each other to become better. Pre-season scrimmages should not be scored in a traditional, regular season-like format. Instead, scrimmages should be scored by accumulating points for successful plays executed by any player from a specific squad against any opposing squad with naturally opposing tasks. This means receivers would be competing two levels up at the Coordinator level, and not among themselves. Building off past research, this should also diffuse anxiety levels of players since each cohesive group will be focused on building up the less talented players, instead of trying to dominate them for increased playing time.